One-dimensional nanotube composite wave-absorbing material with adjustable frequency band magnetic control and preparation method of one-dimensional nanotube composite wave-absorbing material
One-dimensional nanotube iron tetraoxide/manganese tetraoxide composite materials were prepared through hydrothermal synthesis and liquid phase pyrolysis, and directional arrangement was carried out through magnetron rotation, which solved the problems of complex material preparation, high cost and poor stability in the prior art, and achieved efficient electromagnetic wave absorption and multi-band loss enhancement of the material, meeting the needs in the 5G era and wider band environment.
Patent Information
- Application Number
- CN202510098900.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-03-14
AI Technical Summary
The existing adjustable electromagnetic wave absorbing materials have problems such as complex preparation, high cost, poor stability, inaccurate response, and inability to adjust the absorbing frequency band in real time, which cannot meet the needs of the 5G era and in the future wider band electromagnetic wave environment.
One-dimensional nanotube iron tetraoxide/manganese tetraoxide composite material is prepared by hydrothermal synthesis method and liquid phase pyrolysis method, and arranged in a directional manner through magnetron rotation to achieve the frequency band magnetron adjustability of the material.
It has achieved high yield, uniformity, improved magnetic performance and improved electromagnetic wave absorption efficiency of materials, and can achieve enhanced electromagnetic loss in multiple frequency bands, meeting the application needs of the 5G era and in the future wider band electromagnetic wave environment.
Smart Images

Figure CN119612601A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of high-performance composite materials, and in particular to a one-dimensional nanotube composite absorbing material with adjustable frequency band and a preparation method thereof. Background Art
[0002] With the advent of the 5G era, electromagnetic wave technology has been widely used in modern life. The continuous expansion of the communication frequency band has put forward higher requirements for electromagnetic wave absorbing materials. Traditional absorbing materials have gradually exposed their limitations in the multi-band electromagnetic wave environment and cannot meet current needs. Realizing selective absorption of tunable frequency bands in a wider frequency band has become a hot issue that needs to be solved in the field of electromagnetic wave absorbing materials.
[0003] At present, there are two main types of adjustable electromagnetic wave absorbing materials. One is to use a composite of dielectric / magnetic materials. However, this method has many shortcomings. First, the components and structures of the materials need to be carefully proportioned, and the preparation and optimization process is complicated and cumbersome. Secondly, this composite material does not have the ability to adjust in real time, and cannot quickly adjust the absorbing frequency band according to actual needs. Furthermore, there are differences in the response mechanisms of magnetic and dielectric materials under the action of electromagnetic waves, which leads to the absorption capacity of the composite material in certain frequency bands being limited, and its absorbing performance cannot be fully exerted.
[0004] Another type of tunable electromagnetic wave absorbing material uses the fluidity of liquid metal to switch the absorption band. The Chinese patent with publication number CN118399091A discloses a tunable broadband terahertz metamaterial absorber based on 3D printed microchannel liquid metal filling. This solution uses the fluidity of liquid metal to control the injection and discharge of liquid metal in the microchannel cavity layer to change the absorption performance of the metamaterial absorber. This method requires precise design of the microchannel, high preparation and processing costs, and poor chemical stability of liquid metal, which poses a safety hazard.
[0005] In terms of improving the wave absorption properties of materials, structural design solutions are currently usually adopted, such as designing multi-layer, porous and other composite structures. However, this solution also has obvious defects. It involves the optimization and coordination of multiple parameters, the preparation scheme is complex and costly, and the environmental adaptability is poor, making it difficult to meet the needs of electromagnetic wave absorption materials under different environmental conditions.
[0006] In summary, the existing adjustable electromagnetic wave absorbing materials have many problems such as complex preparation, high cost, poor stability, slow response, and inability to adjust the absorbing frequency band in real time. Therefore, designing an electromagnetic wave absorbing material with simple preparation, stable composition, strong coordination, rapid response, and real-time adjustment of the absorbing frequency band has become an important development direction in the current electromagnetic wave absorption field, which is of great significance for meeting the application needs in the 5G era and future wider-band electromagnetic wave environments. Summary of the invention
[0007] In view of this, in order to overcome the deficiencies of the prior art, the present application aims to provide a one-dimensional nanotube composite absorbing material with adjustable frequency band and a preparation method thereof.
[0008] According to the first aspect of the present application, a one-dimensional nanotube composite absorbing material with adjustable frequency band is provided. The material consists of a one-dimensional tubular ferroferric oxide matrix and manganese manganese oxide coated on the outside of the matrix, and is oriented by magnetically controlled rotation.
[0009] According to the second aspect of the application, a method for preparing a one-dimensional nanotube composite absorbing material with adjustable frequency band magnetronics is provided, the preparation method comprising: The iron oxyhydroxide precursor was prepared by a hydrothermal synthesis method; The iron oxyhydroxide precursor is reduced by liquid phase pyrolysis and simultaneously coated with a manganese tetraoxide shell in situ to obtain a nanotube-shaped iron oxide / manganese oxide composite material. Nanotubular ferroferric oxide / manganese manganese oxide composites are oriented and arranged by magnetic field control.
[0010] Optionally, in the method for preparing the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material of the present application, the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material is prepared by reacting ferric chloride, deionized water, oleylamine, tri-n-octylphosphine oxide and manganese acetylacetonate.
[0011] Optionally, the method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetronization of the present application comprises: Dissolve ferric chloride in deionized water to form a clear solution under stirring; The clear solution is subjected to a hydrothermal reaction, and the hydrothermal reaction product is vacuum dried to obtain an iron oxyhydroxide precursor.
[0012] Optionally, in the method for preparing the frequency band magnetically tunable one-dimensional nanotube composite wave absorbing material of the present application, the clear solution is prepared by dissolving 1-11 mmol of ferric chloride in 30 ml of deionized water.
[0013] Optionally, in the preparation method of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material of the present application, the temperature of the hydrothermal reaction is 120°C, the time of the hydrothermal reaction is 4 hours, the temperature of the vacuum drying is 60°C, and the time of the vacuum drying is 10 hours.
[0014] Optionally, the method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetronization of the present application comprises: The iron oxyhydroxide precursor is dispersed in a sufficient amount of oleylamine, tri-n-octylphosphine oxide is added, and then ultrasonic treatment is performed to obtain a mixed dispersion; The mixed dispersion is subjected to liquid phase pyrolysis reaction under a nitrogen atmosphere, and the liquid phase pyrolysis reaction product is centrifugally washed and vacuum dried to obtain a nano-tubular ferrosoferric oxide / manganese manganese oxide composite material.
[0015] Optionally, in the method for preparing the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material of the present application, the molar ratio of the iron oxyhydroxide precursor to tri-n-octylphosphine oxide in the mixed dispersion is 10:1.
[0016] Optionally, in the preparation method of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material of the present application, a liquid phase pyrolysis reaction is performed on the mixed dispersion under a nitrogen atmosphere, and the liquid phase pyrolysis reaction product is centrifugally washed and vacuum dried to obtain a nanotube-shaped ferroferric oxide / manganese manganese oxide composite material, comprising: The mixed dispersion is placed in a nitrogen atmosphere, heated to 220°C at a heating rate of 5°C / min, reacted for 4 hours under stirring, cooled to 180°C, and a mixed solution of manganese acetylacetonate and oleylamine is prepared, wherein the concentration of manganese acetylacetonate in the mixed solution is 0.2-0.5 mol / L, and the molar ratio of manganese acetylacetonate to the iron oxyhydroxide precursor in the mixed dispersion is 1:1-1:2.5; the reaction is continued for 9 hours to obtain a precipitated product; The precipitated product was separated at a rotation speed of 5000 r / min, and after centrifugal washing with cyclohexane, it was vacuum dried at 60° C. for 10 h to obtain a nanotubular ferrosoferric oxide / manganese-manganese oxide composite material.
[0017] Optionally, in the preparation method of the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control of the present application, the nanotubular ferroferric oxide / manganese manganese oxide composite material is oriented and arranged by magnetic field control, including: placing the nanotubular ferroferric oxide / manganese manganese oxide composite material in a mold through a fluid matrix, rotating the mold at different angles and then applying an external magnetic field to obtain the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control.
[0018] The one-dimensional nanotube composite absorbing material with adjustable frequency band and its preparation method of the present application have the following beneficial technical effects: 1. Material preparation and structural advantages High yield and uniformity: One-dimensional tubular ferroferric oxide is prepared by pyrolysis reduction of ferric oxyhydroxide precursor, and combined with surfactant control and manganese tetraoxide coating, a nano-tubular ferroferric oxide / manganese tetraoxide composite material with high yield and uniform shape and size is prepared. This uniform structure lays the foundation for the performance stability of the material, ensuring that the material can maintain consistent electromagnetic wave absorption performance during large-scale production and application.
[0019] Unique tubular structure: With one-dimensional tubular ferroferric oxide as the magnetic core, the tubular structure has lighter mass and higher strength. Compared with traditional block or granular magnetic materials, the tubular structure shows unique advantages in electromagnetic wave absorption. The cavity inside it can form multiple reflections and interface polarization effects, which provides more paths and mechanisms for the propagation and energy dissipation of electromagnetic waves inside the material, thereby effectively improving the electromagnetic wave absorption capacity of the material.
[0020] 2. Magnetic performance improvement and regulation The magnetic permeability is significantly improved: the anisotropy enhancement in the easy magnetization direction of one-dimensional tubular ferroferric oxide can greatly improve the magnetic permeability of the material, making it more sensitive to the magnetic field, and can more effectively guide and regulate the magnetic field component in the electromagnetic wave, thereby enhancing the propagation loss of the electromagnetic wave in the material and improving the magnetic loss performance of the material.
[0021] Electromagnetic control and directional arrangement: After electromagnetic control, one-dimensional tubular ferroferric oxide can form a directional arrangement. This directional arrangement further optimizes the magnetic properties of the material. By orderly arranging the magnetic core, the angle between the magnetic moment and the electromagnetic vector of the electromagnetic wave can be adjusted, thereby obtaining better magnetic loss performance in different frequency bands. This adjustable magnetic property makes it possible to optimize the performance of the material in different application scenarios.
[0022] 3. Improved electromagnetic wave absorption efficiency Dielectric constant adjustment and interface enhanced polarization: By coating the one-dimensional tubular ferroferric oxide magnetic core with manganese oxide, the weakly magnetic manganese oxide can effectively adjust the dielectric constant. Reasonable adjustment of the dielectric constant helps to optimize the electromagnetic matching characteristics of the material, so that the material can better absorb electromagnetic wave energy. At the same time, the introduction of interface enhanced polarization further enhances the material's response to electromagnetic waves. The two components have similar response mechanisms to electromagnetic waves, strong coordination, and rapid response, which can effectively improve the material's electromagnetic wave absorption efficiency, enabling it to achieve efficient electromagnetic wave absorption in a wider frequency band.
[0023] Enhanced electromagnetic loss in multiple frequency bands: By using the magnetically controlled rotation of the one-dimensional ferroferric oxide / manganese oxide composite material to drive the change in the direction of the interface dipole and the easy magnetization moment, the directional arrangement formed can further adjust the electromagnetic parameters of the material. By changing the magnetically controlled rotation angle, the electromagnetic properties of the material can be adjusted in real time, and the impedance matching and loss of the material in each frequency band can be flexibly adjusted according to specific needs. This real-time adjustable characteristic enables the material to achieve enhanced electromagnetic loss in multiple frequency bands, meeting the multi-band absorption requirements of electromagnetic wave absorbing materials in the 5G era and future wider-band electromagnetic wave environments, and providing an effective solution to the problem of limited absorption capacity of current electromagnetic wave absorbing materials in multi-band environments.
[0024] In summary, this application achieves significant improvements in material yield, uniformity, magnetic properties, electromagnetic wave absorption efficiency, and multi-band electromagnetic loss enhancement through a unique material preparation method and structural design. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a scanning electron microscope image of the nano-tubular ferroferric oxide / manganese manganese oxide composite material prepared in Example 1 of the present application; Figure 2 This is a scanning electron microscope image of the nano-tubular ferroferric oxide / manganese manganese oxide composite material prepared in Example 2 of the present application; Figure 3 This is a transmission electron microscope image of the nano-tubular ferroferric oxide / manganese manganese oxide composite material prepared in Example 3 of the present application; Figure 4 This is a complex dielectric constant curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 3 of the present application, wherein: Figure 4 (a) is the curve of the real part of the complex dielectric constant (ε′), Figure 4 (b) is the curve of the imaginary part of the complex dielectric constant (ε″); Figure 5 The complex dielectric constant curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 4, wherein: Figure 5 (a) is the curve of the real part of the complex dielectric constant (ε′), Figure 5 (b) is the curve of the imaginary part of the complex dielectric constant (ε″); Figure 6This is a complex dielectric constant curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 5, wherein: Figure 6 (a) is the curve of the real part of the complex dielectric constant (ε′), Figure 6 (b) is the curve of the imaginary part of the complex dielectric constant (ε″).
[0027] Figure 7 This is a complex magnetic permeability curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 3 of the present application, wherein: Figure 7 (a) is the graph of the real part of complex magnetic permeability (μ′), Figure 7 (b) is the graph of the imaginary part of complex magnetic permeability (μ″); Figure 8 This is a complex magnetic permeability curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 4 of the present application, wherein: Figure 8 (a) is the graph of the real part of complex magnetic permeability (μ′), Figure 8 (b) is the graph of the imaginary part of complex magnetic permeability (μ″); Fig. 9 This is a complex magnetic permeability curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 5 of the present application, wherein: Fig. 9 (a) is the graph of the real part of complex magnetic permeability (μ′), Fig. 9 (b) is the graph of the imaginary part of complex magnetic permeability (μ″); Fig.10 This is a reflection loss diagram of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 3 of the present application in the 1-18 GHz frequency band with a thickness of 0-10 mm, wherein: Fig.10 (a) is the reflection loss projection diagram, Fig.10 (b) is a reflection loss curve; Fig.11 This is a reflection loss diagram of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 4 of the present application in the 1-18 GHz frequency band with a thickness of 0-10 mm, wherein: Fig.11 (a) is the reflection loss projection diagram, Fig.11 (b) is a reflection loss curve; Fig.12 This is a reflection loss diagram of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 5 of the present application in the 1-18 GHz frequency band with a thickness of 0-10 mm, wherein: Fig.12 (a) is the reflection loss projection diagram, Fig.12 (b) is the reflection loss curve. DETAILED DESCRIPTION
[0028] The embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0029] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.
[0030] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.
[0031] Example 1 Step 1: Dissolve 1 mmol of ferric chloride in 30 ml of deionized water, stir until the solution is clear, and transfer the solution to a hydrothermal reactor for hydrothermal reaction at a reaction temperature of 120°C for 4 hours. After the reaction is completed, cool to room temperature, wash the product repeatedly with deionized water and ethanol, and transfer the washed product to a vacuum drying oven for drying at a drying temperature of 60°C for 10 hours to obtain an iron oxyhydroxide precursor; Step 2: Take 1 mmol of the iron hydroxide obtained in step 1 and disperse it in 50 mL of oleylamine, add 0.1 mmol of tri-n-octylphosphine oxide, ultrasonically mix and mix evenly, transfer the mixed dispersion to a flask, introduce nitrogen and heat to 220°C at a rate of 5°C / min, and continue mechanical stirring, and continue to react for 4 hours in a nitrogen atmosphere. After the reaction, reduce the heating temperature to 180°C, slowly add 5 mL of 0.2 mol / L of a mixed solution of manganese acetylacetonate and oleylamine, and continue stirring and reacting for 9 hours in a nitrogen atmosphere. After the reaction, a black precipitate product is obtained. The black precipitate product is repeatedly centrifuged and washed 6 times with cyclohexane at a speed of 5000 r / min. After washing, the product is transferred to a vacuum drying oven for drying at a drying temperature of 60°C and a drying time of 10 hours to finally obtain a nanotubular ferroferric oxide / manganese tetraoxide composite material; Step 3: Grind the dried nanotubular ferroferric oxide / manganese oxide composite material and mix it evenly with paraffin wax, put it into a mold, apply a 30° magnetic field to the material, and obtain a 30° oriented one-dimensional nanotube composite absorber with adjustable frequency band magnetronization. It should be noted that in this application, the fluid matrix can also be a gel or a polymer, etc. At the liquefaction temperature corresponding to the fluid matrix, the composite material is dispersed in a matrix with a certain fluidity such as paraffin wax, gel, polymer, etc., and injected into the mold cavity, and external magnetic fields of different angles are applied to the mold to obtain a one-dimensional nanotube composite absorber with adjustable frequency band magnetronization.
[0032] Embodiment 2: Step 1: Dissolve 5 mmol of ferric chloride in 30 ml of deionized water, stir until the solution is clear, and transfer the solution to a hydrothermal reactor for hydrothermal reaction at a reaction temperature of 120°C for 4 hours. After the reaction is completed, cool to room temperature, wash the product repeatedly with deionized water and ethanol, and transfer the washed product to a vacuum drying oven for drying at a drying temperature of 60°C for 10 hours to obtain an iron oxyhydroxide precursor; Step 2: Take 1 mmol of the iron hydroxide obtained in step 1 and disperse it in 50 mL of oleylamine, add 0.1 mmol of tri-n-octylphosphine oxide, ultrasonically mix and mix evenly, transfer the mixed dispersion to a flask, introduce nitrogen and heat to 220°C at a rate of 5°C / min, and continue mechanical stirring, and continue to react for 4 hours in a nitrogen atmosphere. After the reaction, reduce the heating temperature to 180°C, slowly add 5 mL of 0.3 mol / L of a mixed solution of manganese acetylacetonate and oleylamine, and continue stirring and reacting for 9 hours in a nitrogen atmosphere. After the reaction, a black precipitate product is obtained. The black precipitate product is repeatedly centrifuged and washed 6 times with cyclohexane at a speed of 5000 r / min. The washed product is transferred to a vacuum drying oven for drying at a drying temperature of 60°C and a drying time of 10 hours to finally obtain a nanotubular ferroferric oxide / manganese tetraoxide composite material; Step 3: Grind the dried nanotubular ferroferric oxide / manganese manganese oxide composite material, mix it evenly with paraffin, put it into a mold, apply a 30° magnetic field to the material, and obtain a 30° oriented one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control.
[0033] Embodiment 3: Step 1: Dissolve 11 mmol of ferric chloride in 30 ml of deionized water, stir until the solution is clear, and transfer the solution to a hydrothermal reactor for hydrothermal reaction at a reaction temperature of 120°C for 4 hours. After the reaction is completed, cool to room temperature, wash the product repeatedly with deionized water and ethanol, and transfer the washed product to a vacuum drying oven for drying at a drying temperature of 60°C for 10 hours to obtain an iron oxyhydroxide precursor; Step 2: Take 1 mmol of the oxyhydroxide iron obtained in step 1 and disperse it in 50 mL of oleylamine, add 0.1 mmol of tri-n-octylphosphine oxide, ultrasonically mix and mix evenly, transfer the mixed dispersion to a flask, introduce nitrogen and heat to 220°C at a rate of 5°C / min, and continue mechanical stirring, and continue to react for 4 hours in a nitrogen atmosphere. After the reaction, reduce the heating temperature to 180°C, slowly add 5 mL of 0.5 mol / L of a mixed solution of manganese acetylacetonate and oleylamine, and continue stirring and reacting for 9 hours in a nitrogen atmosphere. After the reaction, a black precipitate product is obtained. The black precipitate product is repeatedly centrifuged and washed 6 times with cyclohexane at a speed of 5000 r / min. The washed product is transferred to a vacuum drying oven for drying at a drying temperature of 60°C and a drying time of 10 hours to finally obtain a nanotubular ferroferric oxide / manganese tetraoxide composite material; Step 3: Grind the dried nanotubular ferroferric oxide / manganese manganese oxide composite material, mix it evenly with paraffin, put it into a mold, apply a 30° magnetic field to the material, and obtain a 30° oriented one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control.
[0034] Embodiment 4: Step 1: Dissolve 11 mmol of ferric chloride in 30 ml of deionized water, stir until the solution is clear, and transfer the solution to a hydrothermal reactor for hydrothermal reaction at a reaction temperature of 120°C for 4 hours. After the reaction is completed, cool to room temperature, wash the product repeatedly with deionized water and ethanol, and transfer the washed product to a vacuum drying oven for drying at a drying temperature of 60°C for 10 hours to obtain an iron oxyhydroxide precursor; Step 2: Take 1 mmol of the iron hydroxide obtained in step 1 and disperse it in 50 mL of oleylamine, add 0.1 mmol of tri-n-octylphosphine oxide (TOPO), ultrasonically mix and mix evenly, transfer the mixed dispersion to a flask, introduce nitrogen and heat to 220°C at a rate of 5°C / min, and continue mechanical stirring, and continue to react for 4 hours in a nitrogen atmosphere. After the reaction, reduce the heating temperature to 180°C, slowly add 5 mL of 0.5 mol / L of a mixed solution of manganese acetylacetonate and oleylamine, and continue stirring and reacting for 9 hours in a nitrogen atmosphere. After the reaction, a black precipitate product is obtained. The black precipitate product is repeatedly centrifuged and washed 6 times with cyclohexane at a speed of 5000 r / min. The washed product is transferred to a vacuum drying oven for drying at a drying temperature of 60°C and a drying time of 10 hours to finally obtain a nanotubular ferroferric oxide / manganese tetraoxide composite material; Step 3: Grind the dried nanotubular ferroferric oxide / manganese manganese oxide composite material, mix it evenly with paraffin, put it into a mold, apply a horizontal magnetic field to the material, and obtain a horizontally oriented one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control.
[0035] Embodiment 5: Step 1: Dissolve 11 mmol of ferric chloride in 30 ml of deionized water, stir until the solution is clear, and transfer the solution to a hydrothermal reactor for hydrothermal reaction at a reaction temperature of 120°C for 4 hours. After the reaction is completed, cool to room temperature, wash the product repeatedly with deionized water and ethanol, and transfer the washed product to a vacuum drying oven for drying at a drying temperature of 60°C for 10 hours to obtain an iron oxyhydroxide precursor; Step 2: Take 1 mmol of the iron hydroxide obtained in step 1 and disperse it in 50 mL of oleylamine, add 0.1 mmol of tri-n-octylphosphine oxide (TOPO), ultrasonically mix and mix evenly, transfer the mixed dispersion to a flask, introduce nitrogen and heat to 220°C at a rate of 5°C / min, and continue mechanical stirring, and continue to react for 4 hours in a nitrogen atmosphere. After the reaction, reduce the heating temperature to 180°C, slowly add 5 mL of 0.4 mol / L of a mixed solution of manganese acetylacetonate and oleylamine, and continue stirring and reacting for 9 hours in a nitrogen atmosphere. After the reaction, a black precipitate product is obtained. The black precipitate product is repeatedly centrifuged and washed 6 times with cyclohexane at a speed of 5000 r / min. After washing, the product is transferred to a vacuum drying oven for drying at a drying temperature of 60°C and a drying time of 10 hours to finally obtain a nanotubular ferroferric oxide / manganese tetraoxide composite material; Step 3: Grind the dried nanotubular ferroferric oxide / manganese manganese oxide composite material powder and mix it evenly with paraffin wax, put it into a mold, and apply a vertical magnetic field to the material to obtain a vertically oriented one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control.
[0036] Example 6 The surface morphologies of the nano-tubular ferroferric oxide / manganese manganese oxide composite materials prepared in Example 1 and Example 2 were observed using a Hitachi Regulus 8100 cold field emission scanning electron microscope, and the acceleration voltage used was 5 kV. Figure 1 This is a scanning electron microscope image of the nano-tubular ferroferric oxide / manganese manganese oxide composite material prepared in Example 1 of the present application. Figure 2 This is a scanning electron microscope image of the nanotubular ferroferric oxide / manganese manganese oxide composite material prepared in Example 2 of the present application.
[0037] Depend on Figure 1 and Figure 2 It can be seen that the nano-tubular ferroferric oxide / manganese manganese oxide composite materials prepared in Examples 1 and 2 of the present application have complete shapes and are evenly distributed.
[0038] The microstructure of the nano-tubular ferroferric oxide / manganese manganese oxide composite material prepared in Example 3 was observed using a JEOL JEM-2100F high-resolution thermal field emission transmission electron microscope. Figure 3 This is a transmission electron microscope image of the nano-tubular ferroferric oxide / manganese manganese oxide composite material prepared in Example 3 of the present application. Figure 3 It can be seen that the ferroferric oxide / manganese-manganese oxide composite material prepared in Example 3 of the present application is a distinct tubular structure, and the outer layer of manganese-manganese oxide is uniformly coated on the ferroferric oxide nanotubes.
[0039] The electromagnetic parameters of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing materials prepared in Example 3, Example 4, and Example 5 were tested using a Keysight PNA-X N5244A vector network analyzer. The testing method was a coaxial cable method, and the testing frequency was in the frequency range of 1-18 GHz. The complex dielectric constant and complex magnetic permeability of each material were obtained, and the reflection loss was calculated using the transmission line method.
[0040] Figure 4 This is a complex dielectric constant curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 3 of the present application, wherein: Figure 4 (a) is the curve of the real part of the complex dielectric constant (ε′), Figure 4 (b) is the curve of the imaginary part of the complex dielectric constant (ε″), which can be expressed as ε r =ε′-jε″ formula; Figure 5 The complex dielectric constant curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 4, wherein: Figure 5 (a) is the curve of the real part of the complex dielectric constant (ε′), Figure 5 (b) is the curve of the imaginary part of the complex dielectric constant (ε″), which can be expressed as ε r =ε′-jε″ formula; Figure 6 This is a complex dielectric constant curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 5, wherein: Figure 6 (a) is the curve of the real part of the complex dielectric constant (ε′), Figure 6 (b) is the curve of the imaginary part of the complex dielectric constant (ε″), which can be expressed as ε r =ε′-jε″ formula.
[0041] pass Figure 4 , Figure 5 and Figure 6It can be seen that when the magnetic field is oriented at 30°, the real part of the complex dielectric constant of the band-adjustable one-dimensional nanotube composite absorbing material prepared in the embodiment of the present application remains near 4.1; when the imaginary part of the complex dielectric constant remains near 0.25, resonance occurs when the frequency is 16.9 GHz, the maximum value of the real part of the complex dielectric constant is 4.37, and the maximum value of the imaginary part of the complex dielectric constant is 0.73. When the magnetic field is vertically oriented, the real part of the complex dielectric constant of the band-adjustable one-dimensional nanotube composite absorbing material prepared in the embodiment of the present application increases in the 1-16 GHz frequency band compared to the 30° orientation, especially in the 15-16 GHz frequency band, an increase of about 12.5%, and the imaginary part of the complex dielectric constant increases significantly in the 15-17 GHz frequency band, an increase of about 31.6%; when the magnetic field is horizontally oriented, the real part of the complex dielectric constant of the material increases in the 1-15 GHz frequency band compared to the 30° orientation, especially in the 14-15 GHz frequency band, an increase of 25%, and the imaginary part of the complex dielectric constant also increases significantly in the 14-15 GHz frequency band, an increase of about 52.4%.
[0042] Figure 7 This is a complex magnetic permeability curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 3 of the present application, wherein: Figure 7 (a) is the graph of the real part of complex magnetic permeability (μ′), Figure 7 (b) is the curve of the imaginary part of complex magnetic permeability (μ″), which can be obtained by μr=μ′-jμ″; Figure 8 This is a complex magnetic permeability curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 4 of the present application, wherein: Figure 8 (a) is the graph of the real part of complex magnetic permeability (μ′), Figure 8 (b) is the curve of the imaginary part of complex magnetic permeability (μ″), which can be obtained by μr=μ′-jμ″; Fig. 9 This is a complex magnetic permeability curve of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 5 of the present application, wherein: Fig. 9 (a) is the graph of the real part of complex magnetic permeability (μ′), Fig. 9 (b) is a graph of the imaginary part of complex magnetic permeability (μ″), which can be obtained from μr=μ′-jμ″.
[0043] Depend on Figure 7 , Figure 8 and Fig. 9It can be seen that the real and imaginary parts of the complex magnetic permeability of the band-adjustable one-dimensional nanotube composite absorbing material show a trend of gradually decreasing with frequency. When the magnetic field is vertically oriented, the real part of the complex magnetic permeability of the material increases in the 1-18 GHz frequency band compared to the 30° orientation, especially in the 2-4 GHz, 9-11 GHz, and 14-18 GHz frequency bands, increasing by about 4.5%. The imaginary part of the complex magnetic permeability also increases significantly in the 1-6 GHz and 8-14 GHz frequency bands, increasing by about 50%.
[0044] Fig.10 This is a reflection loss diagram of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 3 of the present application in the 1-18 GHz frequency band with a thickness of 0-10 mm, wherein: Fig.10 (a) is the reflection loss projection diagram, Fig.10 (b) is a reflection loss curve; Fig.11 This is a reflection loss diagram of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 4 of the present application in the 1-18 GHz frequency band with a thickness of 0-10 mm, wherein: Fig.11 (a) is the reflection loss projection diagram, Fig.11 (b) is a reflection loss curve; Fig.12 This is a reflection loss diagram of the band-adjustable magnetically controlled one-dimensional nanotube composite absorbing material prepared in Example 5 of the present application in the 1-18 GHz frequency band with a thickness of 0-10 mm, wherein: Fig.12 (a) is the reflection loss projection diagram, Fig.12 (b) is the reflection loss curve. As can be seen from the figure, the reflection loss of the horizontally and vertically oriented samples is improved in the whole frequency band compared with the 30° oriented sample, especially in the 12-18GHz frequency band. The reflection loss RL value of the horizontally oriented sample reaches -38.6dB when the sample thickness is 7.5mm and the frequency is 16.2GHz, and the reflection loss of the vertically oriented sample reaches -30.8dB when the sample thickness is 6.7mm and the frequency is 16.6GHz.
[0045] The one-dimensional nanotube composite absorbing material with adjustable frequency band and its preparation method according to the embodiment of the present application have the following beneficial technical effects: 1. Material preparation and structural advantages High yield and uniformity: One-dimensional tubular ferroferric oxide is prepared by pyrolysis reduction of ferric oxyhydroxide precursor, and combined with surfactant control and manganese tetraoxide coating, a nano-tubular ferroferric oxide / manganese tetraoxide composite material with high yield and uniform shape and size is prepared. This uniform structure lays the foundation for the performance stability of the material, ensuring that the material can maintain consistent electromagnetic wave absorption performance during large-scale production and application.
[0046] Unique tubular structure: With one-dimensional tubular ferroferric oxide as the magnetic core, the tubular structure has lighter mass and higher strength. Compared with traditional block or granular magnetic materials, the tubular structure shows unique advantages in electromagnetic wave absorption. The cavity inside it can form multiple reflections and interface polarization effects, which provides more paths and mechanisms for the propagation and energy dissipation of electromagnetic waves inside the material, thereby effectively improving the electromagnetic wave absorption capacity of the material.
[0047] 2. Magnetic performance improvement and regulation The magnetic permeability is significantly improved: the prominent easy magnetization magnetic moment of the one-dimensional tubular ferroferric oxide can greatly improve the magnetic permeability of the material, making it more sensitive to the magnetic field, and can more effectively guide and regulate the magnetic field component in the electromagnetic wave, thereby enhancing the propagation loss of the electromagnetic wave in the material and improving the magnetic loss performance of the material.
[0048] Electromagnetic control and directional arrangement: After electromagnetic control, one-dimensional tubular ferroferric oxide can form a directional arrangement. This directional arrangement further optimizes the magnetic properties of the material. By orderly arranging the magnetic core, the magnetic permeability of the material in a specific direction is enhanced. It also helps to reduce the interaction and energy loss between magnetic domains, thereby obtaining better magnetic loss performance. This adjustable magnetic property makes it possible to optimize the performance of the material in different application scenarios.
[0049] 3. Improved electromagnetic wave absorption efficiency Dielectric constant adjustment and interface enhanced polarization: By coating the one-dimensional tubular ferroferric oxide magnetic core with manganese oxide, the weakly magnetic manganese oxide can effectively adjust the dielectric constant. Reasonable adjustment of the dielectric constant helps to optimize the electromagnetic matching characteristics of the material, so that the material can better absorb electromagnetic wave energy. At the same time, the introduction of interface enhanced polarization further enhances the material's response to electromagnetic waves. The two components have similar response mechanisms to electromagnetic waves, strong coordination, and rapid response, which can effectively improve the material's electromagnetic wave absorption efficiency, enabling it to achieve efficient electromagnetic wave absorption in a wider frequency band.
[0050] Enhanced electromagnetic loss in multiple frequency bands: By using the magnetically controlled rotation of the one-dimensional ferroferric oxide / manganese oxide composite material to drive the change in the direction of the interface dipole and the easy magnetization moment, the directional arrangement formed can further adjust the electromagnetic parameters of the material. By changing the magnetically controlled rotation angle, the electromagnetic properties of the material can be adjusted in real time, and the impedance matching and loss of the material in each frequency band can be flexibly adjusted according to specific needs. This real-time adjustable characteristic enables the material to achieve enhanced electromagnetic loss in multiple frequency bands, meeting the multi-band absorption requirements of electromagnetic wave absorbing materials in the 5G era and future wider-band electromagnetic wave environments, and providing an effective solution to the problem of limited absorption capacity of current electromagnetic wave absorbing materials in multi-band environments.
[0051] In summary, this application achieves significant improvements in material yield, uniformity, magnetic properties, electromagnetic wave absorption efficiency, and multi-band electromagnetic loss enhancement through a unique material preparation method and structural design.
[0052] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A one-dimensional nanotube composite absorbing material with adjustable frequency band magnetronization, characterized in that: The material consists of a one-dimensional tubular ferroferric oxide matrix and manganese manganese oxide coated on the outside of the matrix, and is oriented and arranged by magnetically controlled rotation.
2. A method for preparing a one-dimensional nanotube composite absorbing material with adjustable frequency band magnetronization, characterized in that: The preparation method comprises: The iron oxyhydroxide precursor was prepared by a hydrothermal synthesis method; The iron oxyhydroxide precursor is reduced by liquid phase pyrolysis and simultaneously coated with a manganese tetraoxide shell in situ to obtain a nanotube-shaped iron oxide / manganese oxide composite material. Nanotubular ferroferric oxide / manganese manganese oxide composites are oriented and arranged by magnetic field control.
3. The method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetronization according to claim 2, characterized in that: The one-dimensional nanotube composite wave-absorbing material with adjustable frequency band magnetronization is prepared by reacting ferric chloride, deionized water, oleylamine, tri-n-octylphosphine oxide and manganese acetylacetonate.
4. The method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control according to claim 2, characterized in that: The preparation method comprises: Dissolve ferric chloride in deionized water to form a clear solution under stirring; The clear solution is subjected to a hydrothermal reaction, and the hydrothermal reaction product is vacuum dried to obtain an iron oxyhydroxide precursor.
5. The method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control according to claim 4, characterized in that: The clear solution was prepared by dissolving 1-11 mmol of ferric chloride in 30 ml of deionized water.
6. The method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 120° C., the time of the hydrothermal reaction is 4 h, the temperature of the vacuum drying is 60° C., and the time of the vacuum drying is 10 h.
7. The method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control according to claim 2, characterized in that: The preparation method comprises: The iron oxyhydroxide precursor is dispersed in a sufficient amount of oleylamine, tri-n-octylphosphine oxide is added, and then ultrasonic treatment is performed to obtain a mixed dispersion; The mixed dispersion is subjected to liquid phase pyrolysis reaction under a nitrogen atmosphere, and the liquid phase pyrolysis reaction product is centrifugally washed and vacuum dried to obtain a nano-tubular ferrosoferric oxide / manganese manganese oxide composite material.
8. The method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control according to claim 7, characterized in that: The molar ratio of the iron oxyhydroxide precursor to tri-n-octylphosphine oxide in the mixed dispersion is 10:
1.
9. The method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control according to claim 7, characterized in that: The mixed dispersion is subjected to liquid phase pyrolysis reaction under nitrogen atmosphere, and the liquid phase pyrolysis reaction product is centrifugally washed and vacuum dried to obtain a nano-tubular ferroferric oxide / manganese manganese oxide composite material, including: The mixed dispersion is placed in a nitrogen atmosphere, heated to 220°C at a heating rate of 5°C / min, reacted for 4 hours under stirring, cooled to 180°C, and a mixed solution of manganese acetylacetonate and oleylamine is prepared, wherein the concentration of manganese acetylacetonate in the mixed solution is 0.2-0.5 mol / L, and the molar ratio of manganese acetylacetonate to the iron oxyhydroxide precursor in the mixed dispersion is 1:1-1:2.5; the reaction is continued for 9 hours to obtain a precipitated product; The precipitated product was separated at a rotation speed of 5000 r / min, and after centrifugal washing with cyclohexane, it was vacuum dried at 60° C. for 10 h to obtain a nanotubular ferrosoferric oxide / manganese-manganese oxide composite material.
10. The method for preparing the one-dimensional nanotube composite absorbing material with adjustable frequency band magnetic control according to claim 2, characterized in that: The nano-tubular ferroferric oxide / manganese manganese oxide composite material is oriented and arranged by magnetic field control, including: placing the nano-tubular ferroferric oxide / manganese manganese oxide composite material in a mold through a fluid matrix, rotating the mold at different angles and applying an external magnetic field to obtain a one-dimensional nano-tubular composite wave absorbing material with adjustable frequency band magnetic control.
Citation Information
Patent Citations
Tunable broadband terahertz metamaterial wave absorber based on 3D printing micro-channel liquid metal filling
CN118399091A
Cited By
High-performance composite wave-absorbing material as well as preparation method and application thereof
CN120824556A